Unregistered Marriage in Modern Society: Causes and Its Impact on the Rights of Women and Children on Bawean Island - Faiqatul Insiyah; Abdul Halim; Mustaen (Walidem Institute and Publishing, 2026)
Objective: This study examines the practice of unregistered marriage in modern society on Bawean Island and analyzes the causes and impacts on the fulfillment of women's and children's rights from the perspective of Islamic law and national law. The study aims to identify the social, economic, and religious determinants behind unregistered marriage and explain its legal consequences for the protection of women's and children's rights. Theoretical Framework: This study is based on the concept of marriage as a mitsaqan ghalidan, the theory of family legal protection, and the maqashid al-syari'ah approach that positions marriage registration as an instrument of public welfare. Literature Review: Classical fiqh literature and modern Islamic family law indicate a dualism between sharia validity and administrative legality, where the practice of unregistered marriage has implications for the weak protection of civil rights. Methods: The study used a qualitative socio-juridical and phenomenological approach through in-depth interviews, field observations, and studies of legal documents and population administration. Results: The findings indicate that unregistered marriages on Bawean Island are influenced by economic, cultural, labor migration, and low legal literacy factors, and have a direct impact on women's vulnerability in accessing livelihoods, inheritance, and legal protection, as well as the uncertainty of children's civil status. Implications: This study emphasizes the urgency of marriage registration and the optimization of the marriage validation mechanism as a means of restoring family rights. Novelty: The novelty of the study lies in the integrated analysis of Islamic legal norms, positive law, and the local social realities of the Bawean Island community in explaining the causal relationship between unregistered marriage practices and the protection of women's and children's rights.